In vitro propagation of Vanda orchid: a review - Setiaji, Arkan; Raden Roro Rifka Annisa; Agung Dwi Santoso; Anggiresti Kinasih; Anindita Della Rosa Riyadi (Comunicata Scientiae, 2021)
Vanda for the past decade has been the primadonna of ornamental orchids in the south and southeast Asia, along with Phalaenopsis and Dendrobium. Along with the increase in demand for Vanda, this genus has faced several threats from illegal collection to habitat loss. Mass propagation through in vitro culture is a promising strategy to make ensure sustainable business in horticulture, as well as for conservation purposes. This review provides an overview and synthesizes of various Vanda in vitro culture literature. We showed the researchers' preferences on several aspects for growing Vanda, including species, basal medium, plant growth regulators, explant, and culture conditions. The most commonly used as explants are seeds or protocorms, growing on Murashige & Skoog or Vacin & Went medium. This medium can be added banana homogenate to increase its nutritional value. Vanda seedlings can be incubated at 25 ± 1-3oC, with a lighting intensity of 50 μmol m-2 s-1 at 12/16 h PP. Choosing a medium that is cheaper but still rich in nutrients and its additives especially during the subculture phase; selection of explants that are responsive and minimizing the possibility of contamination; as well as seeing the target market in particular, can make Vanda's propagation efforts more effective, efficient, and profitable.